TO THE SUBJECT OF THE ADMINISTRATIVE RIGHT IN MODERN RUSSIA - A. M. Voronov; A. M. Gogolev (Финансы: теория и практика)
Based on the study of state administration problems typical for modern Russia it is stated that the administrative law should not be reduced exclusively to the administrative and police spheres though the latter are undoubtedly indispensable parts of the administrative law system. The administrative law is substantially wider: it provides a legal framework for the public administration in all spheres of human activities, namely the social and cultural, financial and economic, administrative and political and others; establishes an administrative order and appropriate legal regime the violation of which creates liability of a perpetrator; it studies everything that occurs in the sphere of the state administration. The administrative law to a certain extent and in a specific volume regulates the administration order and procedure in stipulations of the law.